Some aspects of China`s foreign policy securitization through the prism of geopolitical rivalry with the United States in the Asia-Pacific Region: main aspects and dynamics of relations (International relations and international law Journal, 2021)
This article examines the format and dynamics of the strategic relationship between the United States and China, in the context of the Indo-Pacific strategy. Relations between the two countries have become an important and central element of the modern international security system. China’s geopolitical rise as a global superpower has generated a strategic response from the United States. China, within the framework of the emerging multipolar system, seeks to form an international order that is alternative to the American-led. In this regard, within the framework of the increased policy of rivalry between powers, the global geopolitical strategy of the United States focuses on China`s changing status as a regional power transforming to the status of a global, hegemonic stage. Appropriately, this requires the development of specific foreign policy narratives in relation to China, in particular, and the Asia-Pacific, in general. The rise of China and the strengthening of its military power has become an irreversible object of securitization by the United States and its regional allies and partners. The Trump administration has adopted the doctrine of a free and open Indo-Pacific region, which defines China as a revisionist power, and accordingly, based on this definition, a common US strategic line is built. The logic of realism forced the parties to accept the balance of power in their foreign policy calculations, where the parties act to restrain each other. Despite US efforts to contain China, China’s Indo-Pacific strategy is ambiguous. China is aware of its strategic limits within the Asia-Pacific, and therefore has chosen a different strategy. Under the influence of the logic of political realism, the format of relations between China and the United States moved from partnership to the stage of rivalry, which determines the modern strategic narratives between the two countries.Key words: USA, China, Asia-Pacific region, rebalancing, military security, diplomacy, India, Japan.